Chapter 10 Bad behaviours, spoiled identities Face in personality disorders - Peräkylä, Anssi (Taylor & Francis, 2024)
Elaborating on Goffman's ideas of self and face, the chapter examines the ways in which patients with personality disorders manage the stigma of impulsive behaviours (such as verbal or physical violence) in psychiatric assessment interviews. Patients display three different types of stance when they describe their impulsive behaviours. They can (1) show self-reproach through evaluations, verbal marking of the exceptionality of their behaviour, or through bodily displays. They can also (2) lessen the reproach by conveying that there are also moments or aspects of their behaviour when they do not deviate from the norm. Sometimes, however, the patients (3) defy the reproach by showing joy or satisfaction with their impulsive behaviours. The three stance displays correspond to the three strategies of self-management of stigmatised persons discussed by Goffman. While Goffman discussed such strategies at the level of autobiographical time, conversation analysis demonstrates them in micro-interactional time.